Use the Phonetic Methods towards on the Speech Ability Vowel and Consonant (H, K, M, R) for the First Grade of Mentally Disabled Student - Ramadhani, Sayyidatul Luthfiyah Fadhil; Efendi, Mohammad; Sulthoni, Sulthoni (Department of Special Education, 2020)
Use the Phonetic Methods Towards on the Speech Ability Vowel and Consonant (H, K, M, R) for the First Grade of Mentally Disabled Student. This study aims to describe the effect of using the phonetic method on the first grade mentally disabled students' speech ability, especially in the pronunciation of vowel and consonant (h, k, m, r). The method used is Single Subject Research (SSR) with the design of A-B-A. The study results showed that in the baseline-1 phase, the subjects' scores were still low then increased in the intervention phase. The trend increased in the baseline-2 phase and showed stable values in each condition, as well as the results of hypothesis testing with overlapping percentages, which showed results that small, which is 0%. That trend shows that the phonetic method can increase and influence the first-grade mentally disabled student's speech ability.